Introduction to polymer analysis - Crompton, T. R. (Smithers Rapra, 2009)
The aim of this book is to familiarise the reader with all aspects of plastic analysis, and it covers the analysis of the main types of plastics now in use commercially. Introduction to Polymer Analysis gives an up-to-date and thorough exposition of the present state of the art of polymer analysis and, as such, should be of great interest to all those engaged in this subject in industry, university research establishment and general education. It is also intended for undergraduate and graduate chemistry students and those taking courses in plastics technology, engineering chemistry, materials.
Keywords: Plastics -- Analysis.; elektronické knihy; electronic books